2017
DOI: 10.1002/oby.22067
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Obesity, Metabolic Health, and Cancer Mortality

Abstract: Introduction We examined whether metabolic health status increases the risk of cancer mortality, and whether this association varied by body mass index (BMI) category. Methods We performed a prospective study of 22,514 participants from the REasons for Geographic and Racial Differences in Stroke (REGARDS) cohort. We defined metabolic unhealthy status as having 3+ of the following: 1) elevated fasting glucose, 2) high triglycerides, 3) dyslipidemia, 4) hypertension, and 5) elevated waist circumference. We cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…It is also well established in epidemiologic studies that metabolic conditions such as obesity, 342 metabolic syndrome and diabetes are important risk factors for breast cancer and other 343 malignancies [37][38][39][40] and data from animal models offer support to those findings [41,42]. In 344 line with that, we demonstrated that a milieu of metabolic dysfunction and altered stromal 345 microenvironment creates conditions for increased proliferation and survival of both normal and 346 tumorigenic mammary cells as demonstrated by our transplantation studies.…”
supporting
confidence: 78%
“…It is also well established in epidemiologic studies that metabolic conditions such as obesity, 342 metabolic syndrome and diabetes are important risk factors for breast cancer and other 343 malignancies [37][38][39][40] and data from animal models offer support to those findings [41,42]. In 344 line with that, we demonstrated that a milieu of metabolic dysfunction and altered stromal 345 microenvironment creates conditions for increased proliferation and survival of both normal and 346 tumorigenic mammary cells as demonstrated by our transplantation studies.…”
supporting
confidence: 78%
“…AT excess is generated by the imbalance between calories intake and energy expenditure, where energy excess is stored mainly in AT, favoring its expansion. Obesity and overweight, especially abdominal fat accumulation, are major risk factors for a number of noncommunicable diseases including cardiovascular disorders, dyslipidemia, insulin resistance and certain cancers, among others [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the influence of specific metabolic obesity phenotypes on cancers, such as colorectal cancer and breast cancer. 15,16,29,31 Kim et al were the first to explore the incidence of PCa according to the BMI and metabolic status. 32 Both obesity and metabolic disorders increased the risk of PCa, and the risk increased according to the number of components of MetS.…”
Section: Discussionmentioning
confidence: 99%